2016
DOI: 10.1016/j.jmarsys.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Data assimilation of depth-distributed satellite chlorophyll-α in two Mediterranean contrasting sites

Abstract: A new approach for processing the remote sensing chlorophyll-α (Chl-α) before assimilating into an ecosystem model is applied in two contrasting, regarding productivity and nutrients availability, Mediterranean sites: the DYFAMED and POSEIDON E1-M3A fixed point open ocean observatories. The new approach derives optically weighted depth-distributed Chl-α profiles from satellite data based on the model simulated Chl-α vertical distribution and light attenuation coefficient. We use the 1D version of the operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 102 publications
1
7
0
5
Order By: Relevance
“…Contrary to expectations, the main foraging areas in the Ionian Sea during the early chick-rearing phase are not particularly productive and are characterized as lower mesotrophic to oligotrophic (Fig. 5a), with CHL levels of less than 0.10 mg m -3 (Kalaroni et al 2016). These results are in accordance with Cecere et al (2013) who showed that, during chick-rearing, Scopoli's shearwater breeders forage in less profitable areas, closer to their colonies in the central Mediterranean Sea.…”
Section: Discussionsupporting
confidence: 77%
“…Contrary to expectations, the main foraging areas in the Ionian Sea during the early chick-rearing phase are not particularly productive and are characterized as lower mesotrophic to oligotrophic (Fig. 5a), with CHL levels of less than 0.10 mg m -3 (Kalaroni et al 2016). These results are in accordance with Cecere et al (2013) who showed that, during chick-rearing, Scopoli's shearwater breeders forage in less profitable areas, closer to their colonies in the central Mediterranean Sea.…”
Section: Discussionsupporting
confidence: 77%
“…mesocosms; see Sect. 4.8) for the analysis and modelling of specific processes, such as the microbial functioning and the effect of the atmospheric deposition (Christodoulaki et al, 2013;Tsiaras et al, 2017), or for the assimilation algorithms of sea colour data in BGC models (Kalaroni et al, 2016).…”
Section: Biogeochemical Modellingmentioning
confidence: 99%
“…This system uses the coupled physical-biogeochemical model Proudman Oceanographic Laboratory Coastal Ocean Modelling System (POLCOMS)-European Regional Seas Ecosystem Model (ERSEM) of the Mediterranean Sea developed by Holt et al (2008) and updated by Kay and Butenschön (2018), and we applied the PFT assimilation framework developed by Ciavatta et al (2018). Previous applications of ERSEM to investigate the Mediterranean Sea biogeochemistry, in both assimilative and not assimilative simulations, include the works by Vichi et al (1998), Allen et al (1998Allen et al ( , 2002Allen et al ( , 2003, Petihakis et al (1999Petihakis et al ( , 2002Petihakis et al ( , 2007, Triantafyllou et al (2000Triantafyllou et al ( , 2003, Zavatarelli et al (2000), Blackford (2002), Pinardi et al (2003), Kalaroni et al (2016), and Tsiaras et al (2017). A skill assessment was performed to evaluate the reanalysis adequacy in representing the average spatial variability of the phytoplankton community structure.…”
Section: Introductionmentioning
confidence: 99%